Anxiety, Practice Modification, and Economic Impact Among Iraqi Dentists During the COVID-19 Outbreak - Mahdee, Anas F.; Gul, Sarhang S.; Abdulkareem, Ali A.; Qasim, Syed Saad B. (Frontiers in Medicine, 2020)
Objectives: As health care workers on the front line during the coronavirus (COVID-19) pandemic, dental practitioners are amongst those at risk due to their close contact with potentially infected individuals. The aim of the current study was to assess the anxiety, awareness practice modification, and economic impact amongst Iraqi dentists whilst working during the outbreak. Methods: This study was performed using an online survey questionnaire with aid of Google forms from 2nd to 23rd July 2020. A total of 484 clinicians responded. The questionnaire was composed of open end, closed end, and Likert five-point scale questions to assess anxiety, awareness and financial impact of COVID-19 on dentists. Mann–Whitney test was used to compare two groups, whilst Kruskal–Wallis was performed by post-hoc test for multigroup comparisons. Results: The mean age of participants was 36.51 ± 9.164 years and the majority (75.2%) of these were graduate dentists only. More than 80% of participants reported anxiety of catching COVID-19. The recorded anxiety level was higher amongst younger dentists and females. Awareness and practice levels among these dentists of precautions and infection-control measures associated with COVID-19 (94%) was found to be high and to be statistically significantly affected by age, qualification and designation (except GP vs. Specialist). With respect to the economic impact, about 75% of practitioners, regardless of demographical variables, reported that their income had declined by about 50%. Conclusions: The investigation provides clear insights into the anxiety, practice modifications and economic impact on dentists working in Iraq. Although there is a high level of knowledge and awareness of required practice regarding the COVID-19 outbreak among Iraqi dentists, they also reported a high level of anxiety.